Choroidopatia punktowata wewnętrzna – opis przypadku i przegląd piśmiennictwa - Ziaja, Karolina; Kubicka-Trząska, Agnieszka; Karska-Basta, Izabella; Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
We present the case of punctate inner choroidopathy in a 45 years old woman B.S. In the case of PIC we should perform special tests, that may confirm diagnosis, help in the appropriate treatment and avoid complications.